2016
DOI: 10.1016/j.psyneuen.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid concentrations in hair are associated with PTSD symptom severity

Abstract: a b s t r a c tThe endocannabinoid system has been implicated in the regulation of the stress response, fear memory formation, and inflammatory processes. Posttraumatic stress disorder (PTSD) can result from exposure to extreme stress and is characterized by strong, associative memories for the traumatic events experienced. Furthermore, an elevated physical disease risk has been observed in PTSD, likely to be mediated by inflammatory processes. Therefore, altered endocannabinoid regulation can be expected in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 60 publications
4
46
2
3
Order By: Relevance
“…These findings strongly support the involvement of PPARs in the neuropathology of mood and neurodevelopmental disorders [100]. A PPAR-α-allopregnanolone (i.e., endocannabinoid-like/ neurosteroids) cross-talk may have an impact for establishing relevant novel targets for the treatment of PTSD and major depression [9].…”
Section: Neurodevelopmental Disorderssupporting
confidence: 62%
See 1 more Smart Citation
“…These findings strongly support the involvement of PPARs in the neuropathology of mood and neurodevelopmental disorders [100]. A PPAR-α-allopregnanolone (i.e., endocannabinoid-like/ neurosteroids) cross-talk may have an impact for establishing relevant novel targets for the treatment of PTSD and major depression [9].…”
Section: Neurodevelopmental Disorderssupporting
confidence: 62%
“…In the socially isolated mouse, PEA improved contextual fear responses and facilitated contextual fear extinction and fear extinction retention, as well as ameliorated depressive-like and anxiety-like behavior by increasing corticolimbic levels of allopregnanolone [10]. Consistently, in a cohort of Ugandan war survivors affected by PTSD, the hair levels of PEA, oleoylethanolamide (OEA), and stearoylethanolamide (SEA) were found to be decreased when compared with levels of war survivors without current or lifetime PTSD [100], thus suggesting a decreased PPAR-α signal pathway in PTSD. While it is important that these findings will be confirmed also in blood and post-mortem brain of PTSD patients [101], this observation provides support to the involvement of the PPAR-allopregnanolone axis dysfunction in PTSD.…”
Section: Mood Disordersmentioning
confidence: 79%
“…These include alterations in serotonin systems (Southwick et al, 1999), DHEA (Yehuda et al, 2006), neuropeptide Y (Rasmusson et al, 2000), neurosteroids (Morris et al, 2012), endocannabinoids (Wilker et al, 2016) and endogenous opioids (van der Kolk et al, 1989). Genetic work is rapidly expanding, and has identified PTSD-linked polymorphisms in genes encoding elements within the HPA axis (FKBP5 (Binder et al, 2008) and CRHR1 (Amstadter et al, 2011; White et al, 2013; Etkin et al, 2015)), and the sympatho-adrenal system (ADRB2 (Liberzon et al, 2014) and COMT (Boscarino et al, 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…N-palmitoylethanolamine (PEA), an endogenous lipid modulator, is considered part of the extended e-CB next to AEA and 2-AG is considered an analgesic, neuroprotective and antioxidant agent, exerting its pharmacological function by stimulating the peroxisome proliferator-activated receptor -α (PPAR-α), a ligand-activated nuclear receptor [18]. Research has shown that PEA levels in blood show strong negative association with PTSD symptom severity in humans [19] and become increased by antidepressants in corticolimbic regions of rats [20]. Furthermore, PEA binding at PPAR-α interacts with the gamma-aminobutyric acidergic (GABAergic) neurosteroid system in the biosynthesis of allopregnanolone (Allo) [18].…”
mentioning
confidence: 99%